Debonding model for nonlinear Fe-SMA strips bonded with nonlinear adhesives - Li, Lingzhen; Chatzi, Eleni; Ghafoori, Elyas (Engineering fracture mechanics, 2023)
The application of adhesively-bonded joints for strengthening of structures using iron-based shape memory alloys (Fe-SMAs) has recently emerged in construction. Fe-SMAs and the majority of structural adhesives exhibit a pronounced nonlinear material behavior, which may result in a favorable ductile failure mechanism. The development, however, of a mechanical model to predict the structural behavior of the joint is non-trivial due to the presence of nonlinearity in the adherent and adhesive. This study aims to propose a semi-analytical and semi-numerical model for describing the mechanical behavior of Fe-SMA-to-steel adhesively bonded joints. The developed model serves three main functions: (i) estimating the bond capacity for a given interfacial fracture energy, and vice versa; (ii) processing the bond–slip (τ−s) behavior directly from the load–displacement (F−Δ) curve, and vice versa; and (iii) delivering a numerical method to simulate the full-range mechanical behavior of the bonded joints, namely the behavior at different loading stages. The model is validated using the experimental testing of 26 Fe-SMA-to-steel lap-shear joints, as well as 24 further bonded joints subject to shear with different adherents (e.g., stainless steel strips and Nickel–Titanium SMA wires) and base materials (e.g., concrete and composite polymer). An experimental data processing protocol, on the basis of the experimentally measured force–displacement (F−Δ) behavior and the distributed displacement along the bond line (s−x) via the Digital Image Correlation (DIC) technique, is further proposed to assess the full-range behavior of bonded joints. [Display omitted] •Debonding behavior of lap-shear joints comprising nonlinear adherents and adhesives.•An analytical model for bond capacity of joints with nonlinear adherents.•Inference of the bond–slip behavior directly from the load–displacement curve.•A numerical solution for the full-range debonding behavior.•A novel protocol for processing experimentally tested lap-shear behavior.